Structural lesions in the lumbosacral spine in field hockey players - Flis-Maslowska, M.; Trzaska, T.; Wiernicka, M.; Lewandowski, J. (Medicina dello Sport, 2014)
Aim. The present state of knowledge confirms that professional and long practising of competitive sports leads to strains of the locomotor system and back pain. Sports including maximum extension and rotation of the spine may lead to significant strain of the facet joint area. Field hockey is an asymmetrical sport in which the characteristic posture strongly predisposes players to degenerative strain lesions in the spine. The aim of the study was to identify structural lesions of the lumbar spine in field hockey players depending on age and years played. Methods. The study included 80 active field hockey players aged 18-48. Ultimately, 15 junior players (mean age of 20.3±0.98) and 15 senior players (mean age of 36.2±7.54) with back pain were selected. The study subjects were referred to radiological diagnostics of the lumbosacral spine. Results. The results of radiological assessment in both study groups of sportsmen indicated the incidence of congenital anomalies and acquired lesions that can be the cause of pain of the lumbar spine in these players. Conclusion. 1) In active field hockey players, congenital or acquired lesions of the lumbosacral spine were reported; 2) the extent of these lesions is undoubtedly related to the sport practice and years played. Radiological testing should be an important element of diagnostic imaging.